2018
DOI: 10.1002/cpdd.598
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Safety, Tolerability, and Pharmacodynamics of Alicapistat, a Selective Inhibitor of Human Calpains 1 and 2 for the Treatment of Alzheimer Disease: An Overview of Phase 1 Studies

Abstract: Alicapistat is an orally active selective inhibitor of calpain 1 and 2 whose overactivation has been linked to Alzheimer disease (AD). Three studies were conducted in healthy subjects (18-55 years), 1 in healthy elderly subjects (≥65 years), and 1 in patients with mild to moderate AD. Four studies assessed pharmacokinetics, 1 study in healthy subjects assessed pharmacodynamics (sleep parameters, particularly rapid eye movement [REM], as a measure of central nervous system [CNS] penetration and activity), and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“… 197 However, the study was unable to demonstrate a pharmacodynamic effect in the CNS, posing a major risk in further clinical development of the molecule for AD treatment. 205 …”
Section: α-Ketoamide As a Reactive Moiety In Potential Drugsmentioning
confidence: 99%
“… 197 However, the study was unable to demonstrate a pharmacodynamic effect in the CNS, posing a major risk in further clinical development of the molecule for AD treatment. 205 …”
Section: α-Ketoamide As a Reactive Moiety In Potential Drugsmentioning
confidence: 99%
“…Among factors that have held back the field have been: achieving selectivity for calpain‐1; achieving brain bioavailability at concentrations above the IC 50 ; and the question of whether selective calpain‐1 inhibition or inhibition of calpain‐1, calpain‐2, and cathepsin‐B is necessary or desirable [7b] . Very recently, the rationale for the termination of AD clinical trials for the selective calpain‐1 inhibitor, ABT‐957 (alicapistat), was reported as the failure to achieve the pharmacodynamic endpoint [11] . The structure of ABT‐957 was only published very recently, [9e] and after we had completed the synthesis of calpain‐1 inhibitors that contained the ABT‐957 pharmacophore for comparative preclinical studies.…”
Section: Figurementioning
confidence: 99%
“…The selection of interruption of REM‐sleep as a clinical pharmacodynamic endpoint for ABT‐957 was based upon preclinical animal studies in which sleep perturbations were observed for ABT‐957 and were proposed to be a functional consequence of increased extracellular acetylcholine (ACh) [20] . In 17 healthy men aged 25–45 years with regular sleep habits, ABT‐957 failed to achieve this primary endpoint [11] . However, this pharmacodynamic readout does not directly test the calpain‐cathepsin hypothesis, or calpain‐1 engagement.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations